Perceptions about respiratory syncytial virus (RSV) and attitudes toward the RSV vaccine among the general public in China: A cross-sectional survey - Qiang Wang; Shixin Xiu; Liuqing Yang; Lan Li; Min Yang; Xuwen Wang; Yuan Shen; Weibing Wang; Leesa Lin (Taylor & Francis Group, 2024)
ABSTRACTOur study aims to assess the public's perceptions of respiratory syncytial virus (RSV) and attitudes toward the RSV vaccine and to identify associated factors in China. A nationwide cross-sectional survey conducted using an online platform between August 16 and September 14, 2023. Questions related to socio-demographics, awareness, knowledge, perceptions of susceptibility and severity of RSV, and attitudes toward the RSV vaccine were included in the questionnaire. We used the chi-square test and logistic regression model to explore the associated factors. Overall, 2133 individuals were included in this study. Nearly a quarter of participants (24.3%) indicated that they had never heard of RSV. The proportion of individuals aged over 50 years reporting never having heard of RSV (36.5%) and having a low knowledge level of RSV (55.3%) was significantly higher that of other younger age groups. More than half of individuals (55.7%) exhibited low level of perceptions of susceptibility concerning RSV infection. A total of 68.4% of the participants expressed willingness to receive the RSV vaccine. Younger age was positively associated with a higher willingness to be vaccinated. The most frequent reason for declining the vaccine was "Concern about vaccine's safety or side effects." About 60% of individuals considered a price of RSV vaccine below 200 CNY (28 USD) as acceptable. The awareness and perceived susceptibility to RSV infection were limited to the Chinese public. It is necessary to take measures to address the low awareness and knowledge of RSV and acceptability of the RSV vaccine among older adults.